2017
DOI: 10.1093/jme/tjx085
|View full text |Cite
|
Sign up to set email alerts
|

Rodent–Pika Parasite Spillover in Western North America

Abstract: Competition during the Cenozoic expansion of the Rodentia may have contributed to ecological niche reduction of pikas, which are now increasingly under threat as their habitat degrades under global climate change, while some rodents expand their ranges and overlap with pikas. Range overlap carries the possibility of disease spillover. Contemporary North American pikas are cold-adapted and relegated primarily to alpine environments where they subsist on relatively low-quality herbaceous diet. Yet their evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Aetheca wagneri Haddow et al 1983:43 (Central to western U.S.A.), Lewis et al 1988:160–161 (CA, NV, OR, WA), Galloway and Christie 1990:455 (MB), Baird and Saunders 1992:12–13 (ID), Linley, et al 1994:815–817, Larson et al 1996:35 (CA), Ponce-Ulloa and Llorente-Bousquets 1996:561 (México), Larson 1997:3 (ND), Lindsay and Galloway 1997:1313 (MB), Fagelund et al 2001:94 (NM), Smith and Belthoff 2001:160 (ID), Davis et al 2002:110–111 (CA), Ford et al 2004:51–53 (NM), Haas and Kucera 2004:349 (UT), Haas et al (2004:514 (NM), Krasnov et al 2004a:234, 2004b:514, Bossard 2006:262, 264 (none), Morrone and Acosta 2006:2 (México), Foley et al 2017:1253 (none), Bergman et al 2019:18 (BC).…”
Section: Results Systematic Entomologymentioning
confidence: 99%
See 1 more Smart Citation
“…Aetheca wagneri Haddow et al 1983:43 (Central to western U.S.A.), Lewis et al 1988:160–161 (CA, NV, OR, WA), Galloway and Christie 1990:455 (MB), Baird and Saunders 1992:12–13 (ID), Linley, et al 1994:815–817, Larson et al 1996:35 (CA), Ponce-Ulloa and Llorente-Bousquets 1996:561 (México), Larson 1997:3 (ND), Lindsay and Galloway 1997:1313 (MB), Fagelund et al 2001:94 (NM), Smith and Belthoff 2001:160 (ID), Davis et al 2002:110–111 (CA), Ford et al 2004:51–53 (NM), Haas and Kucera 2004:349 (UT), Haas et al (2004:514 (NM), Krasnov et al 2004a:234, 2004b:514, Bossard 2006:262, 264 (none), Morrone and Acosta 2006:2 (México), Foley et al 2017:1253 (none), Bergman et al 2019:18 (BC).…”
Section: Results Systematic Entomologymentioning
confidence: 99%
“…Amaradix bitterrootensis Baird and Saunders 1992:13 (ID), Ford et al 2004:37 (NM), Foley et al 2017:1252–1253 (CO).…”
Section: Results Systematic Entomologymentioning
confidence: 99%
“…Marmots are heavily involved in plague cycles in central Asia, perhaps in polyhostal systems with ground squirrels, voles, and Ochotona pikas (Kalabukhov 1965). Unfortunately, the importance of plague in marmots in the western United States of America has been little studied, but the possibility exists that T. acamantis in high elevation sites may assist in cycling Y. pestis among marmots, PDs, other rodents, and additional hosts, including American pikas (O. princeps), the latter of which are known to carry T. acamantis (Foley et al 2017) and have declined considerably in abundance, perhaps due to plague (Wilkening et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, as pika distributions are moving, often uphill, in response to a warming climate, so are other rodent species, and with those species come new disease threats that pikas have not been exposed to previously. Foley et al (2017) have shown that in high-elevation sites in Colorado and Montana, the diversity of flea species found on pikas includes species that specialize on pikas as well as species that specialize on other rodent species, presumably from contact with those other rodent species.…”
Section: Pikamentioning
confidence: 99%